2002
DOI: 10.1007/s11894-002-0061-8
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic evaluation of complex dysphagic patients: Comparison with videoendoscopic technique

Abstract: Swallowing is a highly coordinated sequence of physiologic events. Many disease processes affect the patient's ability to have a functional swallow. The traditional videofluoroscopic swallowing study is an effective and established method for evaluating these patients and is the current examination of choice. Videoendoscopic evaluation is a safe and affordable procedure that can be used in an outpatient or office setting. It can also be a complementary technique, allowing direct visualization of pharyngeal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
2
0
3
Order By: Relevance
“…Various studies have demonstrated the importance of VF-SS in the diagnosis of dysphagia in relation to a number of diseases [5][6][7][8][9][10][20][21][22][23] and have obtained a good correlation between radiological findings and patient's ALSSS class [24,25]. We correlated ALSSS class of individual patients interviewed with alterations encountered during VFSS: data from our study show a statistically significant difference between the NEH group and the other groups with regard to the oral phase (p=0.036).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have demonstrated the importance of VF-SS in the diagnosis of dysphagia in relation to a number of diseases [5][6][7][8][9][10][20][21][22][23] and have obtained a good correlation between radiological findings and patient's ALSSS class [24,25]. We correlated ALSSS class of individual patients interviewed with alterations encountered during VFSS: data from our study show a statistically significant difference between the NEH group and the other groups with regard to the oral phase (p=0.036).…”
Section: Discussionmentioning
confidence: 99%
“…Diversi autori hanno dimostrato l'importante ruolo svolto dalla VDFG nella diagnosi della disfagia in vari processi patologici [5][6][7][8][9][10][20][21][22][23], ottenendo una buona correlazione fra il riscontro radiologico e la classe ALSSS di appartenenza dei pazienti [24,25]. Abbiamo correlato la classe di appartenenza dei singoli pazienti intervistati alle alterazioni riscontrabili all'esame videofluorografico, e dai dati del nostro studio è stata apprezzata una differenza statisticamente significativa tra il gruppo di pazienti NAA e quello composto dai pazienti degli altri gruppi riguardo le alterazioni della fase orale (p=0,036).…”
Section: Discussioneunclassified
See 1 more Smart Citation
“…The role of videofluorography in identifying swallowing alterations has been codified in a number of studies [4][5][6]8], which also demonstrated how the examination is crucial for revealing aspiration, particularly aspiration not followed by the cough reflex (silent aspiration). A relatively large case series also recently demonstrated how the risk of developing pneumonia is closely correlated with the degree of swallowing dysfunction appreciable at VFSS; in fact, the risk of contracting pneumonia in such patients was calculated to be four times greater than in patients with normal swallowing in the event of laryngeal penetration, ten times greater in the event of aspiration and 13 times greater in the event of silent aspiration [9].…”
Section: Discussionmentioning
confidence: 99%
“…3) e 7 (1 pz) (Fig. 4) della classificazione di Waxmann e pertanto erano posti in nutrizione artificiale con PEG o sondino naso-gastrico; di questi 3 pazienti sono deceduti durante il ricovero, mentre in una paziente è stato possibile togliere la PEG dopo il ciclo di riabilitazione e passarla, alla dimissione, alla dieta con limitazione; nei restanti 6 pazienti non è stato possibile, anche al termine del trattamento riabilitativo, sospendere la nutrizione artificiale.DiscussioneIl ruolo della videofluorografia nella identificazione delle alterazioni della funzione deglutitoria è stato oramai codificato in letteratura da diversi studi[4][5][6]8] nei quali è stato anche dimostrato come l'esame sia fondamentale per la dimostrazione dei fenomeni di aspirazione, specie di quelli non seguiti da tosse (aspirazione silenziosa). Di recente è stato anche dimostrato -in una serie piuttosto ampia di 381 paLaryngeal penetration with barium also in the laryngeal ventricle (risk of aspiration, pharyngeal stasis).…”
unclassified